Language Deception in â€œConfession of a Shopaholicâ€ Movie by Shopie Kinsella - Dian Puspitasari; Fina Amalia Masri (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This thesis aims to analyze language deception found in the utterances of conversations of the characters in Confession of a Shopaholic Movie by Sophie Kinsella. The research question of this study is â€œwhat kinds of language deception are used in Confession of a Shopaholic movie?, The objective of this study is to find the kinds of language deception that used in â€œConfession of a Shopaholicâ€ Movie. The research uses qualitative descriptive as the method of the research. The sources of data in this research are a confession of shopaholic movies directed by Sophie Kinsella and articles, books, and a thesis that can give information related to this research. The data collected through watching, identifying, not taking, screen shooting, reading, and classification. Language deception by Darius Galasinski is used as the theory. The finding shows that there are five kinds of deceptions of Galasinski that are found in the Confession of a shopaholic movie. Those are deception by Omission, evasion, deception by the commission, deception through explicit information, and deception through implied information. There are 15 data found in the movie included the 5 kinds of Galasinski theory of deception. There is deception by omission is 3 data. Evasion is 5 data. Deception by the commission is 2 data. Deception through explicit information is 4 data. Deception through implied information is 1 data. The dominant kind of deception is Evasion. Evasion is deceptive as an attempt to induce in the addressee a false belief as to the relevance of the answer.